2012
DOI: 10.1073/pnas.1205156109
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional repressor PRR5 directly regulates clock-output pathways

Abstract: The circadian clock is an endogenous time-keeping mechanism that enables organisms to adapt to external daily cycles. The clock coordinates biological activities with these cycles, mainly through genome-wide gene expression. However, the exact mechanism underlying regulation of circadian gene expression is poorly understood. Here we demonstrated that an Arabidopsis PSEUDO-RE-SPONSE REGULATOR 5 (PRR5), which acts in the clock genetic circuit, directly regulates expression timing of key transcription factors inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
302
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 271 publications
(317 citation statements)
references
References 47 publications
14
302
0
1
Order By: Relevance
“…Many clock-regulated genes with peak expression in the morning are repressed throughout the day and during the early night by members of the TOC1/PRR1 family of clock proteins. To determine whether the LNKs were regulated by members of this protein family, we reexamined data describing TOC1/PRR1 and PRR5 binding sites in the Arabidopsis genome using ChIP followed by sequencing (ChIP-seq) (31,33). Indeed, we found that the regulatory region of LNK3 was directly bound by TOC1/PRR1 (31).…”
Section: Resultsmentioning
confidence: 99%
“…Many clock-regulated genes with peak expression in the morning are repressed throughout the day and during the early night by members of the TOC1/PRR1 family of clock proteins. To determine whether the LNKs were regulated by members of this protein family, we reexamined data describing TOC1/PRR1 and PRR5 binding sites in the Arabidopsis genome using ChIP followed by sequencing (ChIP-seq) (31,33). Indeed, we found that the regulatory region of LNK3 was directly bound by TOC1/PRR1 (31).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the PIFs themselves are PIF bound, which may be linked to the lightinduced expression of some PIFs, such as PIF7 (Leivar et al, 2008a), PIF4, and PIF5 (Leivar et al, 2009), during deetiolation and suggests the existence of a complex autoregulatory feedback mechanism. PIF4/5 also emerge as direct targets of circadian clock proteins TOC1, PRR5, and PRR7 (Huang et al, 2012;Nakamichi et al, 2012;Liu et al, 2013a), which might contribute to the regulation of the oscillatory expression of PIF4/5 as a repression mechanism complementary to the EC. In addition to the described binding by BZR1 , BRs might also target PIF5 through direct binding by BES1 .…”
Section: Transcriptional Regulation Of the Pifsmentioning
confidence: 99%
“…In the case of cold, the circadian clock regulates the expression and gates the cold induction of the C-repeat binding factors CBF1, 2, and 3, a pathway with a major role in plant cold acclimation and freezing tolerance. The mechanism involves direct CBF induction in the morning by CCA1 and LHY and evening repression by PRR5, 7, and 9 (Dong et al, 2011;Nakamichi et al, 2012). PIF7 and PIF4 also regulate the circadian and diurnal expression of CBFs at warm temperatures, thus potentially participating in the photoperiodic control of the CBF cold acclimation pathway (Kidokoro et al, 2009;Lee and Thomashow, 2012).…”
Section: Interface With the Clockmentioning
confidence: 99%
“…Accumulation of CDF1 mRNA levels is regulated by the transcription-repressing PRR protein family (Nakamichi et al, 2007(Nakamichi et al, , 2012. Mutations of the PRRs resulted in elevated expression of CDF1 (Nakamichi et al, 2007;Ito et al, 2008).…”
Section: Atcdf1 Functions In the Leaf As A Regulator Of Floweringmentioning
confidence: 99%
“…Mutations of the PRRs resulted in elevated expression of CDF1 (Nakamichi et al, 2007;Ito et al, 2008). PRR proteins function in the clock circuit by directly regulating the timing of expression of key TFs involved in clock-output pathways (Nakamichi et al, 2012;Hayama et al, 2017). In Arabidopsis, the PRRs act to promote the floral transition by increasing the rate of FT transcription (Hayama et al, 2017).…”
Section: Atcdf1 Functions In the Leaf As A Regulator Of Floweringmentioning
confidence: 99%